2021
DOI: 10.3390/life11101058
|View full text |Cite
|
Sign up to set email alerts
|

Shift in Conformational Equilibrium Underlies the Oscillatory Phosphoryl Transfer Reaction in the Circadian Clock

Abstract: Oscillatory phosphorylation/dephosphorylation can be commonly found in a biological system as a means of signal transduction though its pivotal presence in the workings of circadian clocks has drawn significant interest: for example in a significant portion of the physiology of Synechococcus elongatus PCC 7942. The biological oscillatory reaction in the cyanobacterial circadian clock can be visualized through its reconstitution in a test tube by mixing three proteins—KaiA, KaiB and KaiC—with adenosine triphosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…We recently reported that KaiC alone undergoes phosphorylation in the absence of Mg 2+ in the reaction mixture. 11,16 Accordingly, ss-KaiC underwent phosphorylation in the absence of Mg 2+ (Figures 2C and S1C). Therefore, we concluded that there is no intrinsic mutantspecific property in ss-KaiC regarding the KaiC-alone phosphorylation and dephosphorylation pattern (Figure 2D).…”
Section: ■ Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…We recently reported that KaiC alone undergoes phosphorylation in the absence of Mg 2+ in the reaction mixture. 11,16 Accordingly, ss-KaiC underwent phosphorylation in the absence of Mg 2+ (Figures 2C and S1C). Therefore, we concluded that there is no intrinsic mutantspecific property in ss-KaiC regarding the KaiC-alone phosphorylation and dephosphorylation pattern (Figure 2D).…”
Section: ■ Resultsmentioning
confidence: 95%
“…Surprisingly, the freshly purified ss-KaiC in the reaction mixture did not show the oscillation, in contrast to wt-KaiC (Figures A and S2A). We reasoned that the freshly purified ss-KaiC did not undergo phosphorylation or dephosphorylation because it had already reached the equilibrium between the two antagonistic reactions . To shift the equilibrium, we dephosphorylated ss-KaiC by incubating it with KaiB at 30 °C overnight.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation